HUBUNGAN PENGGUNAAN GADGET DENGAN PERKEMBANGANSOSIAL ANAK USIA PRA SEKOLAH DI KELURAHAN BARU KECAMATAN LUWUK KABUPATEN BANGGAI - Drova Grano Manorek; Mikaela Delpin Fristalia; Putri Aprilla A (Yayasan Syalom Cipta Sumikolah, 2024)
The Presence Of Gadgets, Especially In The Form Of Smartphones, Has Contributed A Lot In Everyday Life. Gadgets Are A Medium For Finding Information, Interacting, Getting Entertainment, And Even Doing Business Online. The Development Of Information And Communication Technology Greatly Influences ThePsychosocial Development Of Pre-School Age Children. This Study Aims To Identify The Relationship Between Gadget Use And Psychosocial Development In Pre-School Children In The Baru Village, Luwuk District, Banggai Regency. This Research Is A Quantitative Study With A Research Design Using A Cross- Sectional Study Approach In Which The Independent Variables And The Dependent Variable Can Be Measured Simultaneously At The Same Time. Population 35 People With A Sample Using The Total Population. The Sample In This Study Amounted To 35 Samples. The Results Of The Study Found A Relationship Between The Use Of Gadgets And The Psychosocial Development Of Pre-School-Age Children In The Baru Village, Luwuk District, Banggai Regency With A P Value = 0.001 <0.05. Because The Use Of Gadgets With High Intensity Affects The Psychosocial Development Of Children To Be Low, While The Use Of Gadgets With Low Intensity Affects The PsychosocialDevelopment Of Children To Be High. The Conclusion Of This Study Is That There Is A Significant RelationshipBetween The Use Of Gadgets And The Psychosocial Development Of Children In Baru Kelurahan, Luwuk District, Banggai Regency, So It Is Suggested To Parents Who Have Pre-School Age Children To Control And Supervise The Use Of Gadgets For Their Children, To Divide Their Time In Use Gadgets, And Pay Attention To The Applications In The Gadget So As Not To Exacerbate Psychosocial Development In Children.